The Meaning of Time in Surah Al-'Ashr: An Analysis of Ibn Katsir's Tafsir and Its Relevance to Modern Management - Cahyani, Dhea; Nugroho, Kharis; Mustofa, Asrizal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The Qur'an, as the holy book of Muslims, not only contains spiritual and moral guidance but also touches on aspects of human life, including the values of time. Surah Al-'Ashr is a part of the Qur'an, which specifically discusses the value of time and provides profound teachings on the importance of respecting time in the course of human life. This research aims to examine the meaning of time contained in Surah Al-'Ashr through the interpretation approach of Ibn Katsir, a classical mufasir known as the tafsir bi al-ma'tsur approach, which is a method of interpretation based on other verses in the Qur'an, authentic hadiths, as well as the opinions of the companions and tabi'in. Through this approach, Ibn Katsir's interpretation shows that time is not just a chronological dimension, but a living capital that must be used responsibly. This research also relates the values in the surah to modern management practices, such as time management, work character building, and ethical leadership. The results of the study show that the messages of Surah Al-'Ashr have a strong relevance, not only in the religious context, but also in shaping a productive mindset in the contemporary era.